Single nucleotide polymorphism of rs2596542 and the risk of hepatocellular carcinoma development: A meta-analysis. Issue 11 (March 2019) - Kuang, Xue-Jun; Mo, Dun-Chang; Qin, Yan; Ahir, Bhavesh K.; Wang, Jian-Jun; Peng, Zhao; Deng, Zu-Liang
Abstract: Background: Major histocompatibility complex class I-related chain A (MICA) is considered as a tumor antigen, and its expression is affected by its genetic polymorphisms. However, the relationship between rs2596542 polymorphisms in MICA promoter region and hepatocellular carcinoma (HCC) is not fully elucidated so far. This study aims to explore the relationship between single nucleotide polymorphism of rs2596542 and the risk of HCC development through meta-analysis. Methods: MEDLINE, Web of Science, and EMBASE databases were systematically searched to identify relevant studies. A meta-analysis was performed to examine the association between MICA rs2596542 polymorphism and susceptibility to HCC. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated. Results: Fourteen case–control studies involving 4, 900 HCC cases and 19, 519 controls were included. The MICA rs2596542C allele was significantly associated with decreased risk of HCC based on allelic contrast (OR = 0.76, 95% CI = 0.69–0.83, P < .001), homozygote comparison (OR = 0.57, 95% CI = 0.48–0.69, P < .001), and a recessive genetic model (OR = 0.77, 95% CI = 0.65–0.91, P < .001), whereas patients carrying the MICA rs2596542TT genotype had significantly higher risk of HCC than those with the CT or CC genotype (TT vs CT + CC, OR = 1.57, 95% CI = 1.36–1.81, P < .001). Subgroups analyses based on the ethnic or the source of control groups found very similar findings. Conclusion: The C allele in MICA rs2596542 is a protective factor for hepatocarcinogenesis, whereas the T allele is a risk factor. Further large and well-designed studies are needed to confirm this conclusion. Abstract : Supplemental Digital Content is available in the text